2011
DOI: 10.1007/s00033-011-0178-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of rarefied gas flow through a slit at arbitrary pressure ratio based on the kinetic equation

Abstract: A rarefied gas flow through a thin slit at an arbitrary gas pressure ratio is calculated on the basis of the kinetic model equations (BGK and S-model) applying the discrete velocity method. The calculations are carried out for the whole range of the gas rarefaction from the free-molecular regime to the hydrodynamic one. Numerical data on the flow rate and distributions of density, bulk velocity and temperature are reported. Comparisons of the present results with those based on the direct simulation Monte Carl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[2], but it exists only for a gas flow into background gas, see e.g. [3,22]. However, in the present study there is some background pressure at the thicker part of the pipe so that as the flow approaches continuum regime, one can expect the disk to form.…”
Section: Resultsmentioning
confidence: 62%
“…[2], but it exists only for a gas flow into background gas, see e.g. [3,22]. However, in the present study there is some background pressure at the thicker part of the pipe so that as the flow approaches continuum regime, one can expect the disk to form.…”
Section: Resultsmentioning
confidence: 62%
“…The S kinetic model was recently successfully used for simulation of flow of rarefied gases in various geometrical configurations [23][24][25][26][27][28]20,29,30]. However, it should be noted that the H-theorem for this model has been proved only for its linearized form.…”
Section: Kinetic Equationmentioning
confidence: 97%
“…Furthermore, in [11] it was shown that a linearization of the kinetic equation may not be applicable to short and medium length channels: the linearized solution provided an accurate approximation of the mass flow rate in the pressure-driven regime, whereas for the temperature driven flow (thermal creep) a direct nonlinear calculation was required. A range of validity of the linearized method applied for an investigation of a gas flow through a slit at arbitrary pressure drop was studied in [12]. Moreover, in [9] it was found that an application of the linear theory based on the average rarefaction parameter to a gas flow at the large temperature ratio gave a significant error.…”
Section: Introductionmentioning
confidence: 98%